Service quality and the impact on brand image of budget hotels in Melaka, Malaysia / Muhammad Hasbullah Hanif Tajuddin - Tajuddin, Muhammad Hasbullah Hanif (Faculty of Business and Management, 2016)
The recent development of a service quality dimensions provides a mechanism for hotel industry (budget hotel) to promote their accommodation. This quality dimensions concept known as SERVQUAL. They offer an approach to measured service quality of budget hotel and build relationship brand image of companies. Despite its remarkable opportunities claimed by many quarters, the perception of brand image towards budget hotels must be comprehensively examined. This research analyzed the perception of brand image of budget hotel based on service quality namely (tangible, reliability, responsiveness, assurance and empathy). The dimension of service quality to understand its role between service qualities toward brand image of budget hotels. The sample random sampling was used to obtain responses from guest of budget hotels in Melaka Tengah. Result revealed that all independent variable (tangible, reliability, responsiveness, assurance and empathy) was significant relationship with dependent variable (brand image). This research is used descriptive analysis, pearson correlation and simple linear regression to make an analysis of four objectives stated in this study.